Teacher/Researchers in Early Childhood: Ethical Responsibilities to Children - Helen Hedges (Networks: An Online Journal for Teacher Research, 2001)
The 'teacher as researcher' model has been extensively described in other education sectors (eg. Fueyo & Koorland, 1997; Henson, 1996). This model considers the teacher as a researcher in terms of advancing systematic, professional inquiry (Carr & Kemmis, 1986) by focusing inquiry on teaching and learning practices (Keyes, 2000) and problem-solving (Henson, 1996). Knowledge generated by practitioners will be owned by them and perhaps be more likely than formal research to bring improvement to the profession. Teacher/researchers have a vested interest in the outcome of the research, and are likely to continue to review, evaluate and improve practice after the research is complete. This research note focuses on teachers researching children in the early childhood education settings in which they work. Ethical principles to be considered by teacher/researchers are identified and discussed in relation to their application in an early childhood context. Examples from my recent experience as a participant-observer are offered for consideration in relation to practitioner research.